Speech act an approach to Carlos Bulosan's short stories - Gamido, Juliet T. (College of Arts and Letters, University of the Philippines Diliman, 1988)
This thesis is an attempt to analyze two of Carlos Bulosan's short stories. "Be American" and "As Long as the Grass Shall Grow," with the use of the linguistic theory and method known as Speech Act. Of the four major kinds of Speech Act, the focus of this stylistic investigation is centered upon the illocutionary act and perlocutionary act. By individuating the charcter's illocutionary acts within the instantial world of the short stories, the study arrives at the knowledge of how the author effects his intended perlocutionary results in the reader on the real world level.